2020
DOI: 10.1101/2020.06.02.20117739
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

iSCAN: An RT-LAMP-coupled CRISPR-Cas12 module for rapid, sensitive detection of SARS-CoV-2

Abstract: The COVID-19 pandemic caused by SARS-CoV-2 affects all aspects of human life. Detection platforms that are efficient, rapid, accurate, specific, sensitive, and user friendly are urgently needed to manage and control the spread of SARS-CoV-2. RT-qPCR based methods are the gold standard for SARS-CoV-2 detection. However, these methods require trained personnel, sophisticated infrastructure, and a long turnaround time, thereby limiting their usefulness. Reverse transcription-loop-mediated isothermal amplification… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…On the contrary, only a fifth (n = 5 out of 25) of studies that used purified RNA reported less than 90% sensitivity. Among the six studies that used purified RNA samples but has less than 90% sensitivity or specificity [34, 35, 42, 43, 45, 53], three studies have unusual QUADAS-2 risks and concerns, comparing other included studies. Hong et al [35] and Poon et al [43] had high risk of reference standard bias and concern of standard applicability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, only a fifth (n = 5 out of 25) of studies that used purified RNA reported less than 90% sensitivity. Among the six studies that used purified RNA samples but has less than 90% sensitivity or specificity [34, 35, 42, 43, 45, 53], three studies have unusual QUADAS-2 risks and concerns, comparing other included studies. Hong et al [35] and Poon et al [43] had high risk of reference standard bias and concern of standard applicability.…”
Section: Resultsmentioning
confidence: 99%
“…About half of all studies (n = 23 out of 43) have ln(DOR) below that of the pooled data. Eighteen of these studies are those with sensitivity or specificity no more than 90% [26-29, 31, 34, 35, 40, 42, 43, 50, 52, 53, 56, 57, 60, 61, 66]. The other five studies have low ln(DOR) despite having 100% sensitivity and 100% specificity [36, 44, 48, 51, 67].…”
Section: Resultsmentioning
confidence: 99%
“…It is important to consider that the intellectual property behind the RPA method belongs to TwistDx Inc [49], whereas the patent of the LAMP technology has recently expired [50]. Yet, homemade isothermal LAMP enzymes used in the method iScan achieved a significant analytical sensitivity of 10 viral copies per reaction and 100 % of clinical specificity and sensitivity [51], indicating that homemade production of isothermal enzymes perform effectively, efficiently and could reduce costs.…”
Section: Type Of Isothermal Amplification Methodsmentioning
confidence: 99%
“…Also, RT-RPA can be run in parallel (one-pot test) with CRISPR-Cas systems from mesophilic microorganisms. For RT-LAMP, the only way to circumvent the temperature limitation and to develop one-pot methods is using temperature-resistant EnAs-Cas12a (works at 60 ºC) or thermostable AapCas12b, which run simultaneously with the RT-LAMP at 59-62 ºC [26,40,51,52].…”
Section: Time and Temperature Of Isothermal Methodsmentioning
confidence: 99%
“…The Cas13 can be used in point of care setting and it would be low cost when compared to traditional lateral flow assay as it doesn’t require antibody conjugates for the detection (Rauch et al 2020 ). Another effective use of CRISPR Cas 12 was seen by integrating into a lateral flow system named as iSCAN having potential to be used as effective management system for point of care detection(Ali et al 2020 ). AIOD CRISPR assay, made use of a pair of crRNAs to initiate the detection using CRISPR-Cas12a for improved sensitivity.…”
Section: Current Diagnostic Tests For Covid-19mentioning
confidence: 99%